Performance Investigation of Wideband Microwave Frequency Fiber-Optic Multi-Access in Harsh Ambient Environment - Hao Zhang (IEEE Photonics Journal)
The system performance for wideband microwave frequency fiber-optic multi-access is investigated and demonstrated for harsh ambient environment in this article. A theoretical model for noise property, suffering from the temperature variation and mechanical vibration, is established. Via experimental measurements, the performance deterioration of a typical star-topology distribution system is investigated and analyzed in detail. To enhance the capability of the environmental adaptation, phase stabilization and vibration absorption are taken at the optical transmitting end. The temperature-dependent fiber propagation delay is stabilized to suppress the long-term drift. For the mechanical vibration, phase stabilization seems to have no obvious improvement on the fiber link, while vibration absorption can significantly suppress the high vibration frequency at the transmitting end. The results obtained reveals that high-performance wideband microwave frequency multi-access can still be achieved with fiber-optic distribution in the harsh ambient environment, which is full of significance for the field implementation.